Developing rightly culture on TQM - evidence from SMEs in the context of emerging economy - Gorondutse, Abdullahi Hassan (Emerald Group Publishing Limited, 2021)
Total quality management (TQM) must include orientation towards quality awareness in the overall organisational processes in a firm. A successful TQM needs a supportive culture that can adapt to alterations and strengthen innovation. This study aims to confirm the association between the style of management known as organisational culture (OC) and TQM practices in manufacturing Small and Medium Enterprises (SMEs). Data-driven research was drawn from self-assessment inquiries among 772 managers/owners of manufacturing SMEs of the Saudi Arabia Kingdom (KSA). The dominant culture was detected by means of a cross-sectional technique. The findings enrich the literature by revealing a positive effect of OC on TQM execution in the manufacturing SMEs of KSA. Prior to the execution of TQM operations, administrators of manufacturing SMEs should be aware of the culture within organisations so that TQM may be implemented. The study suggests that organisations, particularly manufacturing SMEs, should constantly strive to enhance the TQM culture. Amid intense competition among manufacturing SMEs, it is crucial to guarantee their high performance. This research assists society in evaluating the strength of a particular SME sector and further enables it to assess which SMEs really have a good OC–TQM relation.